P142 Inflammatory bowel diseases associated with primary immunodeficiency: a multicenter study. (21st January 2022) - Malamut, G; Simon, M; Nachury, M; Uzzan, M; Serrero, M; Fumery, M; Trang-Poisson, C; Zallot, C; Abitbol, V; Charbit-Henrion, F; Gornet, J M; Picard, C; et al.
Abstract: Background: Inflammatory bowel diseases (IBD) associated with primary immunodeficiency (PID) remain poorly known. We aimed to isolate characteristics of IBD associated with PID. Methods: Using a GETAID register, we reviewed medical files of recorded patients with PID and IBD (Crohn's disease, ulcerative colitis (UC) or microscopic colitis) followed in 9 adult university hospitals. Results of genetic investigations were available for 46 patients (62%). Results: 74 patients (30 F, 44M) were included with a mean age of 26 years (median: 24 years) at diagnosis of IBD. Forty-four (59%) patients had Crohn's disease with anoperineal lesions in 12, 26(35%) patients had microscopic (mainly lymphocytic) colitis and 4 patients had UC. PID was predominantly antibody deficiency in 40(54%) patients [34 common variable immunodeficiency, 4 X-linked agammaglobulinemia, 2 selective IgA deficiencies], disease of immune dysregulation in 18(24%) patients [CTLA4, LRBA, NFKB1, TNFAi3, XIAP deficiencies, STAT3 and STAT1 hyperactivation], phagocytosis deficiency in 15(20%) patients (12 chronic granulomatous diseases (CGD), 3 congenital neutropenia] and C1s deficiency (n=1). In order of frequency, Crohn's disease was associated with antibody deficiencies (52%), phagocytosis deficiencies (29%) and immune dysregulation (18%), microscopic colitis with antibody deficiencies (65%), immune dysregulation (27%) and more rarely with phagocytosis deficiencies (8%) and UC with antibody deficiencies (75%) and immune dysregulation (25%). 46% of patients received immunoglobulin supplementation, 70% steroids, equally corticosteroids and budesonide, 49% biotherapy mainly anti-TNF-alpha antibody (38%) and ustekinumab (16%), 23% immunosuppressive drugs, mainly azathioprine and sirolimus and 18% aminosalicylates. Three patients (2 CGD, 1 XIAP) had been treated with allogeneic stem cell transplantation (SCT) and one patient (TNFRS13B deficiency) with autologous SCT. Eleven (15%) patients had intestinal surgery, mainly ileocecal resection. During follow-up [mean: 16 years], 51% of patients had transient or sustained clinical remission mainly with an anti-TNF-alpha antibody, ustekinumab, steroids (budesonide) and specific therapy (targeted therapy such as abatacept and ASCT), 41% of patients had severe infections, 22% developed neoplasia mainly gastrointestinal dysplasia and/or cancers (n=8), B cell lymphoma (n=3) and 4 patients died. Conclusion: At adulthood in our series, IBD associated with PID are mainly Crohn's disease and lymphocytic colitis. The first most frequent associated PID is antibody deficiency. Biotherapies (anti-TNF-alpha antibody, ustekinumab), steroids and specific therapies are commonly used to induce clinical remission.